The Effectiveness of Using Interactive Technologies in English Lessons - Tolibayeva Ayjamal Tolibay qizi, (American Journal of Philological Sciences, 2025)
This article explores the effectiveness of interactive technologies in enhancing English language lessons. It examines various digital tools such as interactive whiteboards, language learning applications, virtual classrooms, multimedia resources, and collaborative platforms. The study highlights how these technologies improve learner engagement, facilitate active participation, and support the development of essential language skills. Furthermore, the article provides practical recommendations for educators, including comprehensive teacher training, blended learning approaches, infrastructure investment, student digital literacy development, and feedback mechanisms. By integrating these strategies, English lessons can become more dynamic, personalized, and effective in meeting diverse learner needs.